Penerapan Pencatatan Keuangan Sederhana Menggunakan Aplikasi Digital Google Spreadsheet Dalam Meningkatkan Efisiensi Administrasi Keuangan Pada UMKM Pembuatan Tahu 5 Bersaudara Di Desa Bakaran Batu: Penerapan Pencatatan Keuangan Sederhana Menggunakan Google Spreadsheet - Juliana; Deva Kaila Ardianti; Mita Ananda Aulia; Andini Indah Pratiwi; Siti Nia Ramadhani (Prodi Pendidikan Administrasi Perkantoran UNIMED, 2025)
This study aims to determine the financial administration conditions of the 5 Brothers Tofu Making MSME before using digital recording, describe the implementation of simple financial recording with Google Sheets, and analyze its impact on financial administration efficiency. The study used a qualitative descriptive method with a case study approach through observation, interviews, and documentation. The results showed that before the implementation, financial recording was unstructured, making it difficult for the owner to control cash flow and business profits. After using Google Sheets, recording became more systematic, transparent, and efficient with the automatic calculation feature and cloud-based storage. The conclusion of the study shows that Google Sheets is an effective and affordable solution for MSMEs in improving financial administration efficiency.